Twenty‐five years of epilepsy surgery at a Central European comprehensive epilepsy center—Trends in intervention delay and outcomes - Vít Všianský; Milan Brázdil; Ivan Rektor; Irena Doležalová; Jitka Kočvarová; Ondřej Strýček; Jan Hemza; Jan Chrastina; Eva Brichtová; Ondřej Horák; Patrícia Mužlayová; Markéta Hermanová; et al. (Epilepsia Open, 2023)
Abstract Objective We analyzed trends in patients' characteristics, outcomes, and waiting times over the last 25 years at our epilepsy surgery center situated in Central Europe to highlight possible areas of improvement in our care for patients with drug‐resistant epilepsy. Methods A total of 704 patients who underwent surgery at the Brno Epilepsy Center were included in the study, 71 of those were children. Patients were separated into three time periods, 1996‐2000 (n = 95), 2001‐2010 (n = 295) and 2011‐2022 (n = 314) based on first evaluation at the center. Results The average duration of epilepsy before surgery in adults remained high over the last 25 years (20.1 years from 1996 to 2000, 21.3 from 2001 to 2010, and 21.3 from 2011 to 2020, P = 0.718). There has been a decrease in rate of surgeries for temporal lobe epilepsy in the most recent time period (67%—70%—52%, P < 0.001). Correspondingly, extratemporal resections have become more frequent with a significant increase in surgeries for focal cortical dysplasia (2%—8%—19%, P < 0.001). For resections, better outcomes (ILAE scores 1a‐2) have been achieved in extratemporal lesional (0%—21%—61%, P = 0.01, at least 2‐year follow‐up) patients. In temporal lesional patients, outcomes remained unchanged (at least 77% success rate). A longer duration of epilepsy predicted a less favorable outcome for resective procedures (P = 0.024) in patients with disease duration of less than 25 years. Significance The spectrum of epilepsy surgery is shifting toward nonlesional and extratemporal cases. While success rates of extratemporal resections at our center are getting better, the average duration of epilepsy before surgical intervention is still very long and is not improving. This underscores the need for stronger collaboration between epileptologists and outpatient neurologists to ensure prompt and effective treatment for patients with drug‐resistant epilepsy.